2021
DOI: 10.3390/pharmaceutics13101693
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Release of Poorly Soluble Sulindac with the APTES-Modified SBA-15 Mesoporous Silica

Abstract: The effectiveness of oral drug administration is related to the solubility of a drug in the gastrointestinal tract and its ability to penetrate the biological membranes. As most new drugs are poorly soluble in water, there is a need to develop novel drug carriers that improve the dissolution rate and increase bioavailability. The aim of this study was to analyze the modification of sulindac release profiles in various pH levels with two APTES ((3-aminopropyl)triethoxysilane)-modified SBA-15 (Santa Barbara Amor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…It was suggested that motion, which is characterized by the relaxation times τ 02 = 5.8 × (s) and the activation energy E a 2 = 3.7 (kJ/mol) can be associated with local motion of the methyl group. The third low temperature motion described by the relaxation time τ 03 = 7.8 × (s) and low activation energy E a 3 = 1.8 (kJ/mol) may be related to the jumps of the hydrogen atom in hydrogen bonds, which arise as a result of the interaction of the NH 2 amine groups of the modified silica with the incorporated drug [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was suggested that motion, which is characterized by the relaxation times τ 02 = 5.8 × (s) and the activation energy E a 2 = 3.7 (kJ/mol) can be associated with local motion of the methyl group. The third low temperature motion described by the relaxation time τ 03 = 7.8 × (s) and low activation energy E a 3 = 1.8 (kJ/mol) may be related to the jumps of the hydrogen atom in hydrogen bonds, which arise as a result of the interaction of the NH 2 amine groups of the modified silica with the incorporated drug [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The SBA-15 mesoporous silica was synthesized in accordance with the protocol described by Zhao et al [ 2 ], with modifications presented in our previous study [ 17 ]. The SBA-15 surface modification process was carried out using the grafting method [ 17 ]. Briefly, we dried the silica for 24 h at 110 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this time, the OD values of the GdPO 4 •H 2 O/PLGA, GdPO 4 •H 2 O@SiO 2 /PLGA, GdPO 4 •H 2 O@SiO 2 -APS/PLGA and PBLGg-GdPO 4 •H 2 O/PLGA groups were all higher than those of PLGA, especially the OD values of PBLG-g-GdPO 4 •H 2 O/PLGA cultured cells, which were the highest, with significant differences (p < 0.05). This indicates that the modifiers had good biocompatibility, which may have been the consequence of the positive biocompatibility and biological effects of GdPO 4 •H 2 O, SiO 2 , APS and polyglutamic acid in PBLG [32,[41][42][43][44]. At 7 days of incubation, the OD values of the groups were similar, with only the GdPO 4 •H 2 O@SiO 2 /PLGA and PBLG-g-GdPO 4 •H 2 O/PLGA groups having slightly higher OD values than the glass, GdPO 4 •H 2 O/PLGA and GdPO 4 •H 2 O@SiO 2 -APS/PLGA groups, but there was no significant difference (p > 0.05).…”
Section: Cellular Response 241 Cytotoxicity and Biocompatibilitymentioning
confidence: 95%
“…The most common mesoporous material used as a carrier in drug delivery systems (DDSs) is mesoporous silica and its more advanced forms such as mesoporous silica nanoparticles, mesoporous silica nanorods or bioactive glasses [ 153 , 154 , 155 , 156 ]. Other materials often used for this purpose are mesoporous carbon [ 157 ], mesoporous calcium silicate and mesoporous calcium sulfate [ 150 ].…”
Section: Physicochemical and Biological Characteristics Of Mesoporous...mentioning
confidence: 99%